Dynamics of electronic excitations in YBCO at low temperatures - Fugol, I. Ya.; Samovarov, V. N.; Libin, M. Yu. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
We present the results of low-temperature optical experiments (absorption and reflection) in visible and middle infrared frequency regions with epitaxial films of copper oxide materials like a Y1Ba2Cu3O6+x. Based on our data and reference data, we consider the anomalous spectral effects in HTSC having no analogy with conventional BCS superconductors: (1) the optical response to superconducting transition at Tc; (2) the spectral weight redistribution induced by chemical doping and temperature; (3) the drastic enhancement of low-temperature photodoping; (4) the long spin-structure relaxation via temperature variations seen in the optical spectra. The thorough analysis of the results obtained is fully compatible with the concept of two-component system of light and heavy carriers (holes), being in dynamical coexistence with each other. The dynamical coexistence of the intraband carriers occurs on the background of strongly correlation interrelation of the heavy quasiparticles with the optical interband (charge transfer) excitations.